If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9x = 4x + -2 Reorder the terms: 7 + -9x = -2 + 4x Solving 7 + -9x = -2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + -9x + -4x = -2 + 4x + -4x Combine like terms: -9x + -4x = -13x 7 + -13x = -2 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + -13x = -2 + 0 7 + -13x = -2 Add '-7' to each side of the equation. 7 + -7 + -13x = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -13x = -2 + -7 -13x = -2 + -7 Combine like terms: -2 + -7 = -9 -13x = -9 Divide each side by '-13'. x = 0.6923076923 Simplifying x = 0.6923076923
| 5n-3(3-4n)=39+n | | 14-2x=28 | | 4x-1=13x-32 | | X^2-10+3x=180 | | -3=4-x|5 | | 2x-2=6x-2 | | 4X+12=6x+18 | | y=(-8,-4,3) | | 3u^2=4u+15 | | 4x+5=8-6x | | 4x+3=18X+6 | | |2x-8|=4 | | 5(a+6)-7a=0 | | 16X+8=20X+25 | | -8x-4=-4x+16 | | 12x+16=5x+30 | | x+14=-2x+26 | | x^3-11x^2-20x=0 | | 5x+1=3x+8 | | x+-4=-8 | | -7x-16=-3x-12 | | 5x-11=-2x+31 | | 8x+13=11x-23 | | 24t-.8t^2=90 | | 6x-15=12x+20 | | 5r+3r=10 | | x^3+4x-2=0 | | 24t-8t^2=90 | | 9x+3x-10=3(3x+1) | | 8x^2+29x+15= | | 2/10= | | 4x^2-12x+45=0 |